'Cochlear view' plain radiograph: A simple reliable positioning method. (4th March 2018) - Ambrose, Stephanie Elyse; Todd, Norman Wendell
Abstract : Introduction: The plain 'cochlear view' radiograph for checking cochlear implant electrode coiling and depth of insertion is strongly influenced by positioning. The best accuracy and inter-observer agreement are achieved with the X-ray beam passing through the axis of the modiolus, which is perpendicular to the plane of the basal turn of the cochlea. The basal turn of the cochlea generally is 45 from the head's sagittal plane. Objective: To describe a simple reliable technique of patient positioning to maximize the accuracy of postoperative radiographs in the evaluation of cochlear electrode insertion. Methods: This is a description of patient positioning and radiographic technique for intra-operatively checking the position of the electrode array of a cochlear implant. For the surgery, the patient's head is rolled 60° to the side, and the head stabilized in/on a Mayfield horseshoe headrest. For the X-ray, the operating table is rolled 15° toward the operated ear. The central X-ray beam from the C-arm is directed from near the floor toward the ceiling, aiming for a mark 2 cm anterior to the external auditory meatus. Discussion: Several plain radiograph views have been described to assess cochlear implant electrode array coiling in the cochlea and the depth of insertion of the electrodes. Images away from the 'cochlear view' not only are difficult to interpret but also falsely suggest malposition of the electrode array. The 'cochlear view' radiograph most accurately assessed the depth of insertion. Conclusion: This technique of getting the 'cochlear view' is simple and reliable.